2014
DOI: 10.1111/ppa.12185
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of a new recombinant begomovirus species infecting tomato in theAl‐Batinah region ofOman

Abstract: Whitefly-transmitted begomoviruses are the most important limiting factor for tomato cultivation in Oman, particularly in the Al-Batinah region, the major agricultural area of the country. Commercial farms in the Al-Batinah region were surveyed during January-March 2013. Samples of tomato showing leaf curl disease symptoms typical of begomoviruses were collected and analysed. Full-length sequences of five clones were shown to have relatively low percentage identity values to known begomoviruses, with the highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
(63 reference statements)
0
8
0
Order By: Relevance
“…Not only is this virus the cause of the most significant tomato yield losses in Oman and elsewhere, but recent research has also indicated a more extensive host range (Al Shehi et al, personal communication). The presence of different begomoviruses in crops can raise the probabilities of recombinations occurring, resulting in the formation of new begomovirus species and strains (Al-Shihi et al, 2014). The role of floating row covers then becomes broadened to include not only providing protection against whitefly and thereby reducing epidemics of begomoviruses, but also reducing opportunities for new pathogen variants to arise.…”
Section: Discussionmentioning
confidence: 99%
“…Not only is this virus the cause of the most significant tomato yield losses in Oman and elsewhere, but recent research has also indicated a more extensive host range (Al Shehi et al, personal communication). The presence of different begomoviruses in crops can raise the probabilities of recombinations occurring, resulting in the formation of new begomovirus species and strains (Al-Shihi et al, 2014). The role of floating row covers then becomes broadened to include not only providing protection against whitefly and thereby reducing epidemics of begomoviruses, but also reducing opportunities for new pathogen variants to arise.…”
Section: Discussionmentioning
confidence: 99%
“…OLCOMB was identified in okra with the “Oman” strain of CLCuGeV (Akhtar et al., ). ToLCB is the most commonly encountered betasatellite in Oman, having been identified with a range of viruses including ChLCV, ToLCBrV, ToLCLwV and TYLCV (Al‐Shihi et al., ; Khan, Akhtar, Al‐Zaidi, et al., ; Khan et al., ). ToLCB occurs in Pakistan and India, from where it is believed to have been introduced into Oman (Khan, Akhtar, Al‐Zaidi, et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The Al‐Batinah region produces 68,000–70,000 tons of tomato a year, which is 85% of the total output of the country (Ministry of Agriculture & Fisheries Statistics, 2010, http://www.maf.gov.om). Production of tomato in Oman has been shown to be affected by at least five begomoviruses— Tomato yellow leaf curl virus (TYLCV), Tomato leaf curl Sudan virus (ToLCSDV) , Tomato leaf curl Liwa virus (ToLCLwV; previously known as Tomato leaf curl Al‐Batinah virus), Tomato leaf curl Barka virus (ToLCBrV) and Chilli leaf curl virus (ChLCV) (Al‐Shihi et al., ; Brown et al., ; Khan, Akhtar, Al‐Zaidi, et al., ; Khan, Akhtar, Singh, & Briddon, ; Khan, Akhtar, et al., ). Significantly, the majority of these begomoviruses have their origins outside of Oman and have been introduced relatively recently (Khan, Mansoor, & Briddon, ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have detected Tomato leaf curl Barka virus (ToLCBrV), which is the recombinant between Tomato leaf curl Oman virus (ToLCOMV) and Croton yellow vein virus (CrYVV) (Al-Shihi et al, 2014). These In the virus tree, the positions of the TYLCV-OM, ToLCABV, and ChLCV-OM strains are indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Tomatoes and many other major vegetable crops grown in Oman are susceptible to TYLCV-OM, and disease incidences may reach up to 100% during summer and fall seasons. The incidences of disease are increasing in new crops due to the emergence of recently isolated new recombinants of TYLCV-OM from Oman (Al-Shihi et al, 2014). During a field survey in February 2014, in Albatinah region of Oman, leaf yellowing and rolling with slight crinkling was observed in radish plants, which are indicative of a begomovirus infection.…”
Section: Introductionmentioning
confidence: 99%